Meningkatkan Wisata Kuliner Di Kabupaten Gresik Increasing Culinary Tourism in Gresik City - Widhi Ariestianti Rochdianingrum (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2020)
The tourism sektor is a potential sektor to be developed as one of the sources of income from the original district of Gresik. One of the potential tourism sektors developed in Gresik Regency is culinary tourism. This is due to the many unique and popular culinary from Gresik Regency which has distinctive flavors and made from local ingredients. Making culinary as the main subject in increasing tourism is not an impossible thing to do in Gresik regency, this is because from year to year the number of tourist visits in Gresik district continues to increase. Increasing the number of tourists is a potential that can be used by the Gresik district government to introduce and increase tourist interest in the culinary district of Gresik. The distinctive and popular culinary types in Gresik regency that can be developed include pudak cakes, cubung, ayas, jadah, bonggolan, rumo porridge and salty porridge, krawu rice, processed cross-fish and milk fish, processed fish eggs, intestine martabak, pentol, tofu pickles, sego karak and so forth. Therefore, in this study to formulate strategies that can be done to improve culinary tourism in Gresik district, SWOT analysis is used. Based on the results of the SWOT analysis, it is found that the strategy that can be done to improve culinary tourism in Gresik Regency is to innovate the products produced, optimize tourist attractions to introduce distinctive and popular culinary in Gresik district, and optimize the existing tourism platform, SIPATUGT.